Familiarity with and Preferences for Oral and Long-Acting Injectable HIV Pre-exposure Prophylaxis (PrEP) in a National Sample of Gay and Bisexual Men in the U.S - Parsons, Jeffrey T. (AIDS Behav, 2016)
We sought to determine preferences for oral versus long-acting injectable (LAI) PrEP among gay and bisexual men (GBM). We surveyed a national U.S. sample of 1071 GBM about forms of PrEP. LAI PrEP was found to be acceptable among 43.2 % of men when injected monthly compared with 53.6 % of men when injected every 3 months. When asked to choose between forms of PrEP, 46.0 % preferred LAI, 14.3 % oral, 21.7 % whichever was most effective, 10.1 % had no preference, and 7.8 % would not take PrEP. There were no differences in PrEP preferences by race/ethnicity, income, region of residence, or relationship status. Those unwilling to take PrEP were significantly older than those who preferred LAI PrEP and those who would take either. Those who preferred the most effective form were younger, had less education, and reported more recent club drug use. Those who reported condomless anal sex and those who thought they were good PrEP candidates were more willing to take PrEP. Long-term health and side effects were of the greatest concern for both LAI and oral PrEP. The availability of LAI PrEP has the potential to increase uptake among GBM. The results of ongoing clinical trials of LAI PrEP will need to demonstrate similar or greater efficacy as daily Truvada for uptake to be maximized.